2009
DOI: 10.1176/ps.2009.60.7.965
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Mental Health Admissions to Nursing Homes, 1999–2005

Abstract: Current trends show that the proportion of nursing home admissions with mental illness, in particular depression, has overtaken the proportion with dementia. These changes may be related to increased recognition of depression, availability of alternatives to nursing homes for persons with dementia, and increased specialization among nursing homes in the care of postacute, rehabilitation residents. In light of these trends, it is critical to ensure that nursing homes have resources to adequately treat residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…6 In the United States, since the 1980s there has been a transition from long-stay to post-acute and short-stay NH residents. 16 We expected a similar decreased trend in LOS in time series, but we observed an increased trend. Three main reasons may be related to this increase in LOS.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…6 In the United States, since the 1980s there has been a transition from long-stay to post-acute and short-stay NH residents. 16 We expected a similar decreased trend in LOS in time series, but we observed an increased trend. Three main reasons may be related to this increase in LOS.…”
Section: Discussionsupporting
confidence: 59%
“…If Brazilian LTCIs reorganize themselves to a more health-oriented profile, we should expect a transition to shorter stays due to post-acute care from hospitals as observed in the United States through the 1980s. 16,17 So far, there is still a lack of studies evaluating these institutions in Brazil regarding demographic trends throughout the years.…”
mentioning
confidence: 99%
“…The way that the care for older people with and without dementia is organized may have differed over the years and has certainly been influenced by local and national cultures and political priorities [11,12,13,14], including financial support for public care services. In Western countries, the costs associated with the care of older adults with dementia are mostly related to costs of in-home nursing and nursing home care [1].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies in the United States using three different data sources (Bagchi et al, 2009;Fullerton et al, 2009) concluded that the prevalence rate of a primary diagnosis of mental illness excluding dementia in nursing home residents varied from 4.4% in Medicaid claims to 7% in the National Nursing Home Survey (NNHS). Taking secondary mental illness diagnoses into account, prevalence rates increased to 7% in Medicaid claims, 33.1% in the NNHS, and 46% in the Minimum Data Set (MDS (Morris et al, 1990)) of the Resident Assessment Instrument (Bagchi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%